Remodeling of the Baptist Children's Orphanage. (Trotor, In Southern Ghana) - Boye, Nii Adjetey (2011)
A Thesis Submitted to the Department Of Architecture, Kwame Nkrumah University of Science and Technology in Partial Fulfillment Of the requirements for the degree of Master of Architecture.